Evaluation of domestic wastewater and river management in Belian Village, Batam City Sub-district, Indonesia - Anshah Silmi Afifah; Iva Yenis Septiariva; S Suhardono; I Wayan Koko Suryawan; Mega Mutiara Sari (Regional Development Information Center, Universitas Sebelas Maret, 2023)
Domestic wastewater management is one indicator of sustainable development achievement. Belian Village in Batam City, Indonesia, needs to be evaluated because it has the potential to disrupt environmental conditions. The purpose of this research is to determine the current conditions and make recommendations for domestic wastewater management solutions in Belian Village, Batam City. This study was carried out through direct observation, documentation of activities, and literature searches. From 2014 to 2020, increased access to drinking water and sanitation in Batam City was measured. Despite the increase, it is still observed in Belian Village that wastewater is discharged directly into river bodies. The river's quality will deteriorate as a result of this. To mitigate the negative effects of these activities, communal processing solutions can be implemented. By considering operation and maintenance, an up-flow filter tank can be used for wastewater treatment.